Answer:
Y =
![(X)/(3) - 9](https://img.qammunity.org/2020/formulas/mathematics/middle-school/z7f9o692f7z1iskd12qkbmycvqfud1hi6t.png)
Explanation:
Given equation of first line as
Y = -3X + 4
Slop of the first line (m1) = -3
As first line is parallel to second line , then (m1) × (m2) = - 1
i.e m2 =
![(-1)/(m1)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/31vzf5j7cmtu8iepzvwhwrjye0mh6xea0j.png)
m2 =
![(-1)/(-3)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/3rovasedb7cmks1g5my8rxxllmatpooh03.png)
m2 =
![(1)/(3)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/o08xg954t1gbzo9avralvfomcybk63rm02.png)
Now equation of seconf line with points (9 , -6) and slop
i.e equation of new line Y - y1 = m2 (X - x1)
Y + 6=
![(1)/(3)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/o08xg954t1gbzo9avralvfomcybk63rm02.png)
Y =
![(X)/(3) - (9)/(3) - 6](https://img.qammunity.org/2020/formulas/mathematics/middle-school/fllsg34dfnzmzb0fvetmsgc2pliqfyeg7v.png)
Hence equation of new line is
Y =
Answer